Synonyms: The appendix of SQL/DS? - Eaton, Roger G. (My University, 2016)
As I lay in my hospital room recovering from an emergency appendectomy, the surgeon described the operation. His confidence was comforting; that is, until he tried to explain the purpose of the tissue he had removed from me so hastily. He couldn't find the right words. And as he attempted to convince me that he really did know about appendixes, I concluded that he really didn't know their purpose. His interest in appendixes surfaced only when they became infected.
Citation: Eaton, R. (1992). Synonyms: The appendix of SQL/DS? DATABASE Programming & Design, 5(10) 25-27
Keywords: SQL/DS; Relational Databases; DBMS; Naming Conventions; Security Audits